2004
DOI: 10.1038/sj.bjc.6602207
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial impact of breast/ovarian (BRCA 1/2) cancer-predictive genetic testing in a UK multi-centre clinical cohort

Abstract: This multi-centre UK study assesses the impact of predictive testing for breast and ovarian cancer predisposition genes (BRCA1/2) in the clinical context. In the year following predictive testing, 261 adults (59 male) from nine UK genetics centres participated; 91 gene mutation carriers and 170 noncarriers. Self-report questionnaires were completed at baseline (pre-genetic testing) and 1, 4 and 12 months following the genetic test result. Men were assessed for general mental health (by general health questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
124
4
12

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(150 citation statements)
references
References 39 publications
(37 reference statements)
8
124
4
12
Order By: Relevance
“…Changes in psychological distress after testing in both affected (with cancer) and unaffected BRCA1/BRCA2 mutation carriers reflect mixed results. Some studies have demonstrated shortterm increases in anxiety levels 42,[53][54][55][56] in the first weeks to 1 month post-testing that return to baseline 12 months after testing. Positive BRCA1/BRCA2 results are associated with greater distress in women with breast cancer the closer they are to diagnosis.…”
Section: Impact Of Genetic Test Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in psychological distress after testing in both affected (with cancer) and unaffected BRCA1/BRCA2 mutation carriers reflect mixed results. Some studies have demonstrated shortterm increases in anxiety levels 42,[53][54][55][56] in the first weeks to 1 month post-testing that return to baseline 12 months after testing. Positive BRCA1/BRCA2 results are associated with greater distress in women with breast cancer the closer they are to diagnosis.…”
Section: Impact Of Genetic Test Resultsmentioning
confidence: 99%
“…110 However, cancer worries did not appear to decrease in another study of younger female gene carriers who underwent prophylactic mastectomy and oophorectomy. 54 In a long-term observational study of women with HBOC who underwent RRBSO, overall quality of life At baseline and after testing at 2 wk, 4 mo, 1 y, and 3 y HADS, STAI-State, IES Cancer-specific distress (IES) was increased for carriers 2 wk postnotification compared with baseline (P5.014) but decreased to approximately lower than baseline by 4 mo and 12 mo, and was maintained by 3 y; noncarriers were those who had IES scores that declined from baseline to 12 mo and were maintained at 3 y; mean depression and anxiety scores did not differ between carriers and noncarriers at 3 y and was similar to baseline Bleike 2007 4 Observational, crosssectional; HNPCC; includes men and women Carriers, n531; noncarriers, n525; unknown, n560 (includes inconclusive) 12 mo (mean, 3.8 y) IES Six percent had clinically elevated cancerspecific distress (1 carrier; 1 noncarrier); 4 had clinical HNPCC Abbreviations: BRCA1/BRCA2, breast and ovarian cancer susceptibility genes; CI, confidence interval; CWS-R, Cancer Worry Scale Revised (measures specific distress); GHQ-28, General Health Questionnaire (measures general distress); HADS, Hospital Anxiety and Depression Scale (measures general distress); HBOC, hereditary breast and ovarian cancers; HNPCC, hereditary colon cancer; IES, Impact of Event Scale (measures specific distress-cancer specific); MICRA, Multidimensional Impact of Cancer Risk Assessment (measures genetic testing distress); OR, odds ratio; RRBSO, risk-reducing bilateral salpingooophorectomy; STAI, State-Trait Anxiety Scale (anxiety).…”
Section: Hbocmentioning
confidence: 99%
“…[8][9][10][11][12][13][14] Some studies have demonstrated positive attitudes and support for genetic testing in RD [15][16][17] but the potentially negative psychological consequences associated with predictive testing underline the need for counselling protocols to support families. 15 A strong motivating factor to seek genetic testing for RD has been reported to be the opportunity to access novel therapies 16 but, while such treatments remain unavailable for the vast majority of inherited retinal disorders, testing benefits are likely to centre on improving diagnosis, understanding of inheritance pattern and prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…The study showed that 43 % of all clinically unaffected men altered their cancer surveillance program after testing, and adherence to prostate screening was reported by approximately half of the men. Watson et al (2004) found that men were not negatively affected by genetic testing regarding their general mental health. In women, the rate of prophylactic surgery after genetic testing was higher in carriers than in noncarriers (Schwartz et al 2003;Lynch et al 2006;Loader et al 2004;Antill et al 2006a;Meijers-Heijboer et al 2003;Litton et al 2009;Schwartz et al 2004;Stolier and Corsetti 2005).…”
Section: Familial Breast Cancer (Brca1/2)mentioning
confidence: 96%